Effects of a dance program on psychophysiological variables in hospitalized patients with depression: A mixed model approach. (November 2021) - Polanco-Zuleta, Karen Melissa; Medina-Corrales, Marina; Mendoza-Farías, Franciso Javier; Santos Lozano, Claudia Cristina; Tristán, José; Pappous, Athanasios (Sakis); López-Walle, Jeanette M.
Abstract: This study intended to examine the effects of two programs, pharmacological treatment vs. pharmacological treatment + Dance Program (DP), on the perception of self-efficacy, depression, and heart rate variability (HRV) in hospitalized patients with major depressive disorder (MDD); The primary caregiver's perception was also considered and recorded. The sample consisted of 27 patients (pharmacological = 14 and pharmacological + DP = 13) who were admitted to the IMSS Psychiatric Hospital, with a diagnosis of MDD. There was a significant increase in the perception of self-efficacy in the pharmacological + DP group after treatment ( Z  = 3.19, p  < .01), but not in the pharmacological group ( Z  = 0.126, p  > .01). Regarding depression, a greater decrease was found in the pharmacological + DP group. In HRV there were differences only in heart rate, showing a reduction due to the impact of the time factor and the time and group factor. As for the results of the interview with primary caregivers, their perceptions indicate that dance is an activity that can fortify the recovery process of their family members. In conclusion, a dance program of moderate to vigorous intensity in conjunction with pharmacological treatment reduces depressive symptoms and increases the perception of self-efficacy, resulting in a greater benefit for the recovery of depressive patients. Similarly, the primary caregivers involved in this study highlighted the importance of the dance program as an option to support the standard treatment of depression. Highlights: Few studies relate DP to self-efficacy in depressed hospital patients. Information about self-efficacy, MDD and HRV in depressed hospital patients. DP allows to improve psychophysiological aspects in depressed hospital patients. It links the primary caregiver's perspective on DP in depressed hospital patients.